Skrining Penyakit Degeneratif Lansia melalui Pemeriksaan Kolesterol, Asam Urat, dan Gula Darah - Oktaviani, Fifin; Candra, Heldi; Muliana, Hilda; Kusumawati, Aldhehita Ari; Putri, Lita Riastienanda (-, 2026)
The increasing proportion of the elderly population has led to a shift in disease patterns toward chronic and degenerative non-communicable diseases. This issue is particularly critical in island areas with limited access to health services, where delayed detection of degenerative diseases among older adults is more likely to occur. This community service activity aimed to describe the results of degenerative disease screening as an early detection effort among elderly residents of Pulau Kasu, Belakang Padang District, Batam City. The activity was conducted through health screening of 92 elderly participants by measuring total cholesterol, uric acid levels, and random blood glucose, accompanied by health education and individual counseling. The screening results showed that 41% of participants had elevated cholesterol levels, 29% had increased uric acid levels, and 23% exhibited high random blood glucose levels. These findings highlight the importance of community-based health screening as an initial strategy for preventing and controlling degenerative diseases among the elderly in island communities.